2015
DOI: 10.3390/en8031685
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Offshore Wind Energy and Extreme Wind Speed Forecasting on the West Coast of Taiwan

Abstract: It is of great importance and urgency for Taiwan to develop offshore wind power. However, relevant data on offshore wind energy resources are limited. This study imported wind speeds measured by a tidal station and a buoy into the software WAsP to estimate the high-altitude wind speeds in the two areas. A light detection and ranging (Lidar) system was set up near the tidal station and buoy. High-altitude wind speeds measured by the Lidar system were compared with the WAsP-estimated values, and it was discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In general, Taiwan is very open to foreign direct investment and knowledge sharing. Efforts have been rendered within academia to assist the Taiwanese government to map out the potential for offshore wind electricity generation in Taiwan and to analyze the extreme wind speeds experienced on the West Coast of Taiwan [64]. Also, academia has provided useful answers regarding alternative types of foundations for deeper waters such as modified jacket foundations suitable for local conditions and seabed structures in Taiwan [65].…”
Section: Our Asian Case Study Work Outside Chinamentioning
confidence: 99%
“…In general, Taiwan is very open to foreign direct investment and knowledge sharing. Efforts have been rendered within academia to assist the Taiwanese government to map out the potential for offshore wind electricity generation in Taiwan and to analyze the extreme wind speeds experienced on the West Coast of Taiwan [64]. Also, academia has provided useful answers regarding alternative types of foundations for deeper waters such as modified jacket foundations suitable for local conditions and seabed structures in Taiwan [65].…”
Section: Our Asian Case Study Work Outside Chinamentioning
confidence: 99%
“…At 7 s, the wind speed reached 12 m/s and was kept constant, which is the rated wind speed for the FRC-WT with PMSG. The active power output of the offshore wind farm also ramped up to the maximum power level [33][34][35][36][37]. An SLG fault between the cable, the sheath, and the ground was simulated on the 33-kV collector feeder 1, with a fault impedance of 0.01 Ω.…”
Section: Case Studymentioning
confidence: 99%
“…Among renewable energy technologies, offshore wind is regarded as one of the most attractive renewables to be developed. According to the wind speed data measured by a tidal station and a buoy on the west coast of Taiwan, the wind speeds at a height of 100 m are approximately 9.32 to 11.24 m/s [1]. It was found that the coastal areas west of Taiwan are rich in wind energy resources.…”
Section: Introductionmentioning
confidence: 99%